Association Between Charlson Comorbidity Index and Community-Acquired Pressure Injury in Older Acute Inpatients in a Chinese Tertiary Hospital - Zhang Z (Dove Medical Press, 2021)
Zhili Zhang,1,* Hongli Yang,2,* Man Luo3 1Department of Surgical, Wuhan Third Hospital Affiliated to Wuhan University, Wuhan, 430070, People’s Republic of China; 2Department of Public Health, The First Community Health Service Center of Guanshan, Wuhan, 430073, People’s Republic of China; 3Department of Nursing, Wuhan Third Hospital Affiliated to Wuhan University, Wuhan, 430070, People’s Republic of China*These authors contributed equally to this workCorrespondence: Man LuoDepartment of Nursing, Wuhan Third Hospital Affiliated to Wuhan University, Wuhan, 430070, People’s Republic of ChinaTel +86 18207139227Fax +86 27-88850381Email lm229603580@163.comPurpose: To explore the correlation between community-acquired pressure injury (CAPI) and comorbidities in elderly patients with emergency admission.Patients and Methods: Patients aged 65 years or above were enrolled from multiple departments, such as Internal Medicine, Surgery, Geriatrics, and Intensive Care Unit of Wuhan Third Hospital, which is affiliated to Wuhan University, from January to December 2020. Comorbidity data were extracted using the 10th edition of the International Classification of Diseases (ICD-10) from the hospital electronic medical record system, and the Charlson Comorbidity Index (CCI) was calculated using these data. Participants were divided into two groups according to whether pressure injury was present at admission. The baseline characteristics of the two groups were compared using Student’s t-tests, Mann–Whitney U-tests, and chi-square tests. Univariate and multivariate logistic regression models were constructed to explore the relationship between CAPI and the CCI. Smooth curve fitting was used to show the relationship between the CCI and CAPI. By drawing the receiver operating characteristic curve, the CCI was used to predict CAPI.Results: A total of 5759 participants with an average age of 75.1 ± 7.6 were included in this population-based study. The prevalence of CAPI was 4.3%. In logistic regression analysis, there was a positive relationship between the CCI and CAPI after adjustment for sex, age, hypoproteinemia, and anemia (OR = 1.37, 95% CI = 1.29– 1.45, p < 0.001, trend test p < 0.001). The area under the receiver operating characteristic curve was 0.75, and the maximum value of the Youden index was 0.35, with a critical value of 5.5.Conclusion: The development of CAPI was positively correlated with the CCI. The risk of developing pressure injury increases with the number and severity of comorbidities. This study shows that the CCI has certain reference value in predicting CAPI.Keywords: aged, comorbidity, chronic disease, frailty, pressure ulcer, present on admission